Peningkatan Kecakapan Vokasional dan Hasil Belajar Siswa Melalui Pembelajaran Kimia Berbasis Kewirausahaan - Nourma Yulita; Mohammad Agus Prayitno (Jurnal Penelitian Pendidikan IPA, 2023)
Vocational skills are one of the skills that students must have in facing today's industrial world. Therefore, schools should provide lessons that can improve students' vocational skills. One way to develop vocational skills is through chemistry learning based on Chemo-entrepreneurship (CEP). This research aims to determine the influence of CEP-based chemistry learning on students' vocational skills and learning outcomes. The method used in this research was a quasi-experiment with a pretest-posttest control group design. This research was conducted at MAN 1 Rembang. The research sample consisted of 48 students consisting of 23 students as the control group and 25 students as the experimental group. The research results showed that the N-gain of vocational skills in the control group was 0.31 while the experimental group was 0.55. The N-gain of the control group's learning outcomes was 0.04 while the experimental group was 0.53. The results of the t test for vocational skills and learning outcomes obtained a score of t count > t table (2.01), namely 3,462 and 6,932. The conclusion of this research is that CEP-based chemistry learning has a positive influence in improving vocational skills and student learning outcomes.